Sequence-specific affinity selection of mammalian splicing complexes. - Ryder, U (1990)
Antisense oligonucleotides made of 2'-OMe RNA are shown to bind specifically and efficiently to targeted sites on pre-mRNA substrates, allowing affinity selection of splicing complexes using streptavidin/biotin chromatography. The position of probe binding to the pre-mRNA influences which type of splicing complex can be selected. The accessibility of pre-mRNA sequences to antisense probes changes during the course of the splicing reaction. U1, U2, U4, U5 and U6 snRNAs are all detected in affinity-selected mammalian splicing complexes. However, antisense oligonucleotides targeted to snRNAs can block the binding of specific snRNPs to pre-mRNA. Quantitative affinity selection analyses show that only a small fraction of snRNPs in a HeLa nuclear splicing extract participate in spliceosome formation.